2004
DOI: 10.1088/0022-3727/37/12/008
|View full text |Cite
|
Sign up to set email alerts
|

Calculation of the effective gas interaction probabilities of the secondary electrons in a dc magnetron discharge

Abstract: In sputter magnetrons the electrons emitted from the target, the so-called secondary electrons (SE), can be recaptured by the target. As a result, not all emitted SE will interact with the discharge gas. The effective gas interaction probability (EGIP) is the probability that an emitted SE interacts with the discharge gas, and thus is not recaptured by the target. To calculate the EGIP an analytical model is developed. The model is verified by comparing its results with those of a Monte Carlo model.The EGIP of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 19 publications
(32 reference statements)
4
30
1
Order By: Relevance
“…However, since the electron mean free path is inversely proportional to pressure, at the low gas pressures of a magnetron discharge [42,54,55], a significant number of these electrons can return to the cathode and be recaptured without producing ionizations. The effect of electron recapture on the argon discharge characteristics has been discussed in a simplified [54] and a detailed model of the dc planar magnetron [42].…”
Section: Effect Of Electron Recapture At the Cathodementioning
confidence: 99%
See 2 more Smart Citations
“…However, since the electron mean free path is inversely proportional to pressure, at the low gas pressures of a magnetron discharge [42,54,55], a significant number of these electrons can return to the cathode and be recaptured without producing ionizations. The effect of electron recapture on the argon discharge characteristics has been discussed in a simplified [54] and a detailed model of the dc planar magnetron [42].…”
Section: Effect Of Electron Recapture At the Cathodementioning
confidence: 99%
“…The influence of different discharge parameters on the discharge voltage during magnetron sputtering has been recently discussed by Depla et al [55] who compiled a list of electron emission yields for several metals from experimental data and empirical formulas found in literature [47,56,57]. As seen in Fig.…”
Section: Effect Of Electron Recapture At the Cathodementioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Knowledge of the ion-induced secondary electron emission coefficient ␥ e and the ion-induced negative O − ion emission coefficient ␥ O − is also essential for the understanding and the modeling of the plasma sheath potential 5,6 and the magnetron discharge. 7 The secondary electron emission induced by low energy ions, i.e., up to a few hundred of eV, is already well understood for clean metallic surfaces. 8,9 In contrast, due to the complexity of the measurements, the mechanism responsible for electron emission of insulators and/or oxides is so far not yet fully understood.…”
mentioning
confidence: 99%
“…13,22 When this happens, they can be reflected or absorbed depending on the reflection coefficient ͑RC͒, given as the number of electrons that are reflected back in the discharge versus the number of incident electrons, and which is thus given by a value between 0 and 1. It is shown that this recapture of secondary electrons has a great effect on the discharge characteristics.…”
Section: Reflection Coefficient and Secondary Electron Emission Comentioning
confidence: 99%